Fuzzy Technique for Order Preference by Similarity to Ideal Solution Based Optimization for Grid-Connected Solar PV System - Hazrul, Mohamad Basri; Abdulhamid Sani, Iliyasu; Kasumawati, Lias; Yonis M Yonis, Buswig; Wan Azlan, Wan Zainal Abidin; Hazlie, Mokhlis; Saad, Mekhilef (Semarak Ilmu Publishing, 2025)
This study presents an optimization framework for grid-connected solar photovoltaic (PV) systems using the Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (F-TOPSIS). With the growing demand for sustainable energy solutions, the research addresses the dual objective of maximizing power output while minimizing capital costs under architectural, financial, and energy constraints. A detailed case study involving real world building parameters and energy consumption data was conducted, evaluating 17 PV system configurations. The F-TOPSIS method was applied to rank these alternatives based on fuzzy-weighted criteria of power generation and budget limitations. Results indicate that the optimal configuration—utilizing 230 panels arranged across 10 MPPTs— achieves a balanced trade-off between performance and cost, delivering 129.6 kWp at a capital cost of RM334,025. The study demonstrates the effectiveness of the fuzzy decision making approach in handling uncertainties in multi-criteria PV system design and provides a systematic methodology for selecting the most viable solar PV configuration.